Coupling coal pyrolysis with char gasification in a multi-stage fluidized bed to co-produce high-quality tar and syngas. (1st April 2018) - Chen, Zhaohui; Li, Yunjia; Lai, Dengguo; Geng, Sulong; Zhou, Qi; Gao, Shiqiu; Xu, Guangwen
Graphical abstract: Highlights: A multi-stage fluidized bed was proposed to couple coal pyrolysis with char gasification. This work succeeded in the smooth operation of multi-stage fluidized bed. Char gasification provided heat and gas atmosphere for coal pyrolysis. The flow direction of volatile against temperature ascending avoided the deep secondary reaction of tar. Coupling pyrolysis and gasification could achieve the coal staged conversion. Abstract: A multi-stage fluidized bed (MSFB) by configuring the distributor with an overflow standpipe between its neighboring stages was developed to couple the powder coal pyrolysis with its resultant char gasification for co-production of tar and syngas. This work succeeded in the smooth operation of MSFB for coal staged conversion. The three modes of coupling pyrolysis and gasification in terms of the one-stage, two-stage and three-stage bed characterized by temperature drop from the bottom up were investigated to evaluate the quality of the liquid and gas products. Coupling low- and mid-temperature tandem coal pyrolysis with high-temperature char gasification in the MSFB improved the quality of tar and syngas. The obtained tar yield was over 80% of the Gray-King assay tar yield and its light tar fraction (boiling point <360 °C) was as high as 70–80% in the MSFB. Syngas with CH4 content of 5.2 vol.% was produced that was suitable for SNG production. Inside the reactor, the flow direction of pyrolysis volatiles toward the temperature drop avoided the deep secondary reaction of tar. Syngas and steam from the bottom gasification section could contribute to the formation of light tar and CH4 by affecting the top coal pyrolysis. A comparison with the typical pyrolysis processes suggested that the MSFB process had its own advantages in treating powder coal to produce the high-quality tar and syngas.